Evaluación fitosanitario de plantaciones de capirona (Calycophyllum spruceanum) en el caserío 3 de Octubre, distrito de San Juan Bautista, Loreto, Perú, 2021 - Mera Lopez, Israel Vietnam (2022)
The study was carried out in the hamlet of "3 de Octubre" located at km. 21 of the Iquitos - Nauta highway, San Juan Bautista district, Maynas province, Loreto region, in five plantations ("A", "B", "C", "D" and "E") of forty 40 individuals of the Capirona species (Calycophyllum spruceanum), installed in 2019, with the aim of determining the phytosanitary parameters: survival, mortality, vigor, insect damage, signs and symptoms, to know its current status. The distance between the individuals was 12 m x 24 m in an area of 1.15 ha, with a total of 200 individuals in the five plantations. The results indicate that the survival was 146 individuals (73 %) and the mortality was 54 individuals (27 %), the average vigor of the plantations is 1.8 in the very vigorous category, with a tendency to vigorous, that is to say with good foliage and color, plus great coverage and appearance. As for damage by insects, the presence of grasshoppers (Orthopteros) of the Tettigoniidae family and beetles, belonging to the Chrysomeloidea family, presenting a healthy category, with an average of 0.3, was found. The presence of signs and symptoms was not very significant in the plantations, but the total fall of the leaves, wounds or perforations present in some of the leaves and wilting were found. Finally, the general phytosanitary status of the five plantations is 1.1, located in the healthy category. After the evaluation and analysis of the sanitary parameters, it will be eliminated that the phytosanitary status of the Capirona plantation (Calycophyllum spruceanum), is in the healthy category with an average of 1.1.